Neuromarketing: The neuroadvertising (the new marketing tools) - Flores Tamayo, Hilton Aníbal (Teoría y Praxis, 2022)
The article is an assessment of the evolution of marketing and advertising up to the use of techniques taken from the study of neurosciences. The simple appreciation of rationality as an indicator of the logical buying behavior of a consumer is far from the reality of their behavior. The neurosciences are advanced in deciphering how emotions affect the actions of individuals and to what extent the rational is faced with irrationality at the time of making a purchase. This seeks to improve techniques and means for the advertising message to be more effective, developing strategies that combine the use of traditional tactics, valued with neural studies of behavior in certain situations of consumer purchase.